Fusarium stalk rot incidence in maize, Zea mays L., in relation to the European corn borer, Ostrinia nubilalis (Hubner) infestation, genotype maturity and eastern Ontario climatic gradient. - Meloche, François. (University of Ottawa (Canada), 1997)
Development of maize, Zea mays L., germplasm resistant to the European corn borer, Ostrinia nubilalis (Hubner) and Fusarium fungal pests has been in progress for more than three decades as a worldwide cooperative effort. Some of the host plant resistance to the European corn borer and Fusarium has been attributed to the phytochemical product 6-methoxybenzoxazolinone. However, it has been shown that seasonal weather impacts concurrently on maize development, corn borer and Fusarium phenology. It was hypothesized that some of the maize resistance to both pests depended directly on climatological conditions. In the United States, genotype selection for first generation borer resistance is achieved during June infestations using leaf feeding assessment. In Canada, first selection began at the silk stage of plant development in July. The second genotype selection is conducted at grain harvest in October by plant dissections. The larval population, number of tunnels and tunnel length in the first 30 cm of the stalk above the soil surface were used to differentiate genotype susceptibility to corn borers. Grain moisture was directly correlated with genotype resistance to corn borer. Fungi encountered comprised Fusarium moniliforme, F. graminearum, F. sporotrichioides, F. oxysporum, F. avenaceum, and F. equiseti. Two species, F. moniliforme and F. equiseti, were recovered throughout the season. These fungi were first recovered from pollen caught in the leaf collar sheath. As the leaf sheath of maize is relaxed with plant development, the Fusarium contaminated soil and the pollen run down past the ligule by wind, rain splash, and insect movement to settle within the sheath cavity. Undamage pith samples (by the borer) taken at grain harvest showed sporadic tissue contamination by Fusarium. Oppositely, as the corn borer larvae migrated downward on the plant, they drilled the collar sheath, the stalk rind and dug galleries in the stalk to feed on the pith tissue to complete their development. Consequently, the larvae and borer tunnels were repeatedly contaminated with Fusarium. It was shown that pith tissues were initially colonized by primary fungi such as F. equiseti which initiate pith breakdown; then these fungi were overgrown by more competitive species such as F. moniliforme or F. sporotrichioides. Correlation of the stalk rot incidence to genotype maturity and the stalk rot incidence to grain moisture were both negative and significant; indicating that physiological activity during October protected the stalk against fungi infection. It was hypothesized that genotype maturity based on the heat unit rating (given by companies) or grain moisture at harvest (indicator of genotype maturity) were the two common factors related to Fusarium stalk rot resistance. (Abstract shortened by UMI.)
Keywords: Agriculture, Agronomy.